Binding of HSA to Macromolecular pHPMA Based Nanoparticles for Drug Delivery: An Investigation Using Fluorescence Methods - Zhang, Xiaohan; Chytil, Petr; Etrych, Tomáš; Liu, Weiwei; Rodrigues, Leticia; Winter, Gerhard; Filippov, Sergey K; Papadakis, Christine M (Langmuir, 2018)
Amphiphilic poly( N-(2-hydroxypropyl)methacrylamide) copolymers ( pHPMA) bearing cholesterol side groups in phosphate buffer saline self-assemble into nanoparticles (NPs) which can be used as tumor-targeted drug carriers. It was previously shown by us that human serum albumin (HSA) interacts weakly with the NPs. However, the mechanism of this binding could not be resolved due to overlapping of signals from the complex system. Here, we use fluorescence labeling to distinguish the components and to characterize the binding: On the one hand, a fluorescent dye was attached to pHPMA, so that the diffusion behavior of the NPs could be studied in the presence of HSA using fluorescence lifetime correlation spectroscopy. On the other hand, quenching of the intrinsic fluorescence of HSA revealed the origin of the binding, which is mainly the complexation between HSA and cholesterol side groups. Furthermore, a binding constant was obtained.
Keywords: Nanoparticles; sérový albumin; makromolekulární látky; vazba proteinů; nosiče léků; Drug Carriers; Humans; Serum Albumin; lidé; Macromolecular Substances; Serum Albumin, Human; Spectrometry, Fluorescence; Protein Binding; nanočástice; lidský sérový albumin; fluorescenční spektrometrie